A Literatura infantil indígena como meio de promoção da educação multicultural: a intervenção didática em uma escola de Belém (Brasil) - SALES, Maria da Luz Lima (Universidade de Évora, 2022)
The research presented as a central theme the indigenous children's literature as the means of propagation of the multicultural education, considering the Brazil as context of violence and prejudice against indigenous peoples that live in this country even before the colonization in 1500 by the Portuguese. Of a qualitative and naturalist nature, the investigation used semi structured interviews to students of the fourth year of elementary in a Belem's (Brazil's) school on the first semester of 2017, composing basically of two parts and with different objectives. At first, it was attempted to know on the students the attitudes and concepts about the peoples and indigenous cultures realizing our reality in relationship to the culture and indigenous literature. Second, it was attempted to achieve the level of knowledge of the students in relationship to that culture, encouraging higher respect by the Brazilian native as well as for their culture. Was used, in addition to the research in documents and observations collected in field notes, the intervention in classroom, united on ten workshops in which was applied the histories of children's indigenous literature narrated both as indigenous writers as non-indigenous writers and also a lot of others didactic resources in order to innovate the practices on the scholar environment and so decrease prejudiced attitudes and intolerant in relationship to indigenous societies and their ethos, causing these can be respected and valued in fullness. Conclusively, were found shorts modifications that compose the conceptions of the child-subjects in relationship to the indigenous culture. Such changes, although aren't absolute, indicate didactic actions like this, next to a constant work and systematic about the literature and indigenous culture that may contribute successively for a change of position of the society in relationship to the indigenous peoples.